ILLUMINATION The development and implementation of lighting concepts into a physical car - Johansson, Markus (My University, 2014)
This report covers the exploration of how illumination can be used in cars to create customer value and affection. The work was conducted at the Department of Body and Trim at Volvo Cars in Torslanda, Gothenburg and featured an interdisciplinary approach that mixed computer- and design engineering. The project was launched as a step in Volvo’s ambition to become a premium car brand in an industry where illumination is by many considered a forgotten area. The purpose was to generate and implement innovative interior and exterior concepts into a car that would serve as a source of inspiration and discussion for personnel at Volvo. The work was introduced with a pilot study, aiming to narrow the scope and create a more specific theme when later generating ideas. This phase resulted in one design- and one technical vision that stated that the light in the car should express life, temper and character, resulting in a vehicle that felt intuitive, respondent and alert. The following idea generation phase included several workshops and discussions with people inside and outside Volvo and resulted in a total of 24 ideas of which 12 were built into a final demo car named Strix. These built in concepts blended small function oriented features, such as a buckle finder, with large conceptual visions that involved analysis of how future car driving would be like. The lighting techniques used in these concepts included Power LEDs, optical fibers, photo luminescent pigment and different light transporting mediums. Looking at the final result, the Strix project was perceived as successful. While not all objectives defined at the start could be fulfilled, the general impression was that the project succeeded in its stated main purpose, i.e. creating inspiration and discussion at Volvo. The automotive industry has a long way to go when it comes to taking advantage of the possibilities with illumination, but Volvo has started the work and the concepts demonstrated in the Strix might very well develop into something that is implemented in future production cars.
Keywords: Data- och informationsvetenskap; Computer and Information Science